Tantangan dalam Penerjemahan Berita Daring - Pamungkas, Muhammad Ersan Pamungkas (Kementerian Sekretariat Negara Republik Indonesia, 2019)
This research discusses the translation of online news articles from Indonesian into English on the official website of the Cabinet Secretariat (www.setkab.go.id). Data collected are three news articles and their translations in English. This research is a qualitative research in the field of translation studies. The result of this study indicates that in the translation of news from the Cabinet Secretariat website, three main translation problems are identified, namely the translation of the headline, providing additional information in the translation, and the translation of the news lead. The research also finds that in translating online news, translators often not only translate the news online, but also rewrite the news in the TL. Keywords: translation, translator, online news, rewriting.